Assistance relationships humanization in Dental Ethics Code - Lucato, Maria Carolina; de Paula Ramos, Dalton Luiz (O Mundo da Saúde, 2006)
Technical and scientific progress made over the last decades promoted a fast development of Health Sciences, including Odontology, for the benefit of the patients’ health. On the other hand, this tremendous progress drew the attention of health professi- onals to the developments, making more impersonal their relationship with patients. People need to be considered as the whole they are, and so professionals must develop their interpersonal skills to behave accordingly, especially when faced with people made more vulne- rable by their pains and sufferings, as it is very often the case in the field of Odontology. With that purpose in view, this work used a hermeneutic method to assess the Code of Dental Ethics currently in force _ the Resolution 42/2003 _ concerning the promotion of more humane assistance care services. The interpretation of this norm enabled to conclude that the draft of the code in reference, which was elaborated at the 3rd Brazilian National Conference on Dental Ethics [“III CONEO”] was concerned with the care given to the patients’ health and with the respect held for their dignity, both of which are fundamental precepts for the humanization of assistance care services. Finally, the work concluded that the Code would nevertheless gain in being less repetitive on some issues and in having a more defined purpose, while emphasizing the concept of human being.